The impacts of the EU ETS on Norwegian plants' environmental and economic performance - Marit E. Klemetsen; Knut Einar Rosendahl; Anja Lund Jakobsen (Statistics Norway, Research Department, 2016)
This paper examines the impacts of the EU Emissions Trading System (ETS) on the environmental and economic performance of Norwegian plants. The EU ETS is regarded as the cornerstone climate policy both in the EU and in Norway, but there has been considerable debate regarding its effects due to low quota prices and substantial allocation of free allowances to the manufacturing industry. Both quota prices and allocation rules have changed significantly between the three phases of the ETS. The rich data allow us to investigate potential effects of the ETS on several important aspects of plant behavior. The results indicate a weak tendency of emissions reductions among Norwegian plants in the second phase of the ETS, but not in the other phases. We find no significant effects on emissions intensity in any of the phases, but positive effects on value added and productivity in the second phase. Positive effects on value added and productivity may be due to the large amounts of free allowances, and that plants may have passed on the additional marginal costs to consumers.
Keywords: C23; C54; D22; Q54; Q58; 330; Tradable emissions quotas; emissions intensity; productivity; propensity score matching; difference-in-differences